PROGRAM RUMAH SABUN SEBAGAI UPAYA BERBASIS MASYARAKAT DALAM MENGATASI PERMASALAHAN STUNTING - Nasrul Hadi Purwanto; Riska Aprilia Wardani; Rina Widiyawati (Jurnal AbdiMas Nusa Mandiri, 2026)
The problem of stunting that occurs in the community tends to occur due to the inability of the community, especially families, to meet the nutritional needs of toddlers during growth and development. To resolve this problem, one effort that can be done is to stimulate the community, especially families of stunted toddlers, to become economically empowered. One of these efforts is by providing productive skills combined with education related to stunting. The implementation method of the activity is focused on a collaborative and practical approach, starting with coordination with the Village Government to identify participants, followed by entrepreneurship training that includes interactive lectures on stunting and hands-on training in making dish soap, laundry soap, and softener. Through this method, the activity aims to create new sources of income for families as a practical step in stunting prevention efforts. The Rumah Sabun community service activity has succeeded in improving the technical skills of 23 participants in producing dish soap, laundry soap, and softener, which previously did not have any at all. The evaluation results showed a significant increase, where 34.8% of participants (8 people) were categorized as capable and 65.2% (15 people) were categorized as quite capable, so that there were no longer any unskilled participants. As a form of sustainability, this program goes beyond training and has also pioneered the formation of community-based entrepreneurial groups, assisted by the village government and academic volunteers. This collaboration also facilitates local product marketing, ensuring that this activity is not only a successful empowerment intervention but also creates a sustainable micro-enterprise ecosystem to support family economic growth, a strategic step in stunting prevention.